If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying z + z + z + -10 = -1 Reorder the terms: -10 + z + z + z = -1 Combine like terms: z + z = 2z -10 + 2z + z = -1 Combine like terms: 2z + z = 3z -10 + 3z = -1 Solving -10 + 3z = -1 Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '10' to each side of the equation. -10 + 10 + 3z = -1 + 10 Combine like terms: -10 + 10 = 0 0 + 3z = -1 + 10 3z = -1 + 10 Combine like terms: -1 + 10 = 9 3z = 9 Divide each side by '3'. z = 3 Simplifying z = 3
| 6+3w=4w | | 18(7-2n)=1(7+2n) | | 3+2p=17 | | 3x+4=28x-78 | | 4x+42-5x=2-8x-5 | | 747=2.4x^2+90.8x+1.59 | | X^3+X^2=576 | | 4t=1.6 | | -13t=-117 | | x-10y=-10 | | B-7.5=1 | | 160=112t-16t | | 6-p=5p+30 | | T-2.2=3.1 | | -3c=3 | | 9w=5(w-14) | | 25x^3-5x^2+8x+2=0 | | -21=y+y+y | | 7.5=m+5 | | N+1.6=2.8 | | -2(5-7x)=-150 | | 81u^2-u^2v^4= | | 15=6n | | 6(8+a)=15(1+a) | | 7x-2x=x+9+x | | 6x-(4x+7)=14-5 | | -3c=-117 | | y-2x+4=-7x+4x^2 | | 5t=6 | | 6x+2x=10x+12-4x | | 2n+5(2n+3)= | | 700+60x=400+60x |